Analgesic and anti-inflammatory activities of combrang (Nicolaia speciosaHoran) stem the extract - Susilowati, Sri Sutji; Martono, Sudibyo; Riyanto, Sugeng; Nugroho, Agung Endro (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Long-term goal of this study is the use of combrang (Nicolaia speciosa Horan) as an ingredient of traditional medicine after being evaluated through preclinical testing and clinical trials both extract and its bioactive compounds. This study includes analgesic-antiinflammatory activity test of n-hexane, chloroform, ethyl acetate and methanol extract of combrang stem. Analgesic test against crude extract of n-hexane, chloroform,ethyl acetate and methanol, using acetate writhing method. Antiinflammatory test using inhibition method of paw oedema by carrageenan induced on Wistar rats. Analgesic-antiinflammatory activity compared to Na-diclofenac. The result is four extracts have analgesic and antiinflammatory activity, ethyl acetate extract has the highest analgesic and antiinflammatory activity.Key words: analgesics, anti-inflammatory, extract of combrang stem